Anticardiolipin antibodies from syphilis and systemic lupus erythematosus induce leakage in cardiolipin vesicles - Gremiao, MPD; Celli, C. M.; Chaimovich, H. (Associação Brasileira de Divulgação Científica (ABRADIC), 1996)
Anticardiolipin antibodies from sera of patients with systemic lupus erythematosus or syphilis induced leakage of entrapped carboxyfluorescein (CF) from cardiolipin (CL)/phosphatidylcholine(PC) vesicles prepared by sonication of equimolar mixtures of CL:PC. The sera dilution used here was 1:7500. IgG (5-20 mu g/ml) from the same sera, not containing beta(2)GPI, also produced a concentration-dependent leak. Vesicle leakage was inhibited by salt and was not detected with vesicles prepared exclusively with phosphatidylcholine. The demonstration of antibody-induced vesicle leakage offers a convenient system to investigate the mechanism of antibody-lipid binding as well as a potential diagnostic tool.
Keywords: anticardiolipin antibodies; cardiolipin; vesicles; syphilis; systemic lupus erythematosus; carboxyfluorescein